To Grow or Not to Grow? That is the Question: Lessons for Social Ecological Transformation from Small-Medium Enterprises - Heidi Leonhardt; Juschten Maria; Clive L. Spash (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2017)
While research on alternatives to growth at the level of the economy as a whole is accumulating, few studies have related the criticism of growth to the business level. This paper starts to address this gap by investigating mechanisms of growth for small and medium sized enterprises (SMEs), presenting a case study that applies Q methodology and interviews with owner-managers of both growing and non-growing SMEs in Austria. Some mechanisms stimulating growth are identified across SMEs including contributing to innovativeness and motivation of employees. Others are only of relevance for some SMEs: competition, financial stability and a desire for market power. The owner-managers of non-growing SMEs hold values and pursue goals that free them from mechanisms of growth or prevent them from being triggered. Moreover, they exhibit a strong identification with their SME, operate in niche markets and strive for financial independence. This illustrates that a growth imperative is neither inevitable nor are growth mechanisms always operative, but depend upon structures and institutions.
Keywords: L21; M14; O44; 330; SME growth; growth mechanisms; post-growth society; social ecological transformation